Employing Technology in Prehistoric Archaeology: Improving Positioning and Documenting Finds in the Gafsa Region (Sebha University Conference Proceedings, 2024)
Employing technology in prehistoric archaeology remains crucial to tangible progress, as platforms such as Google Maps and Google Earth have played a prominent role in accurately identifying old data, contributing to important new discoveries. Since 1909, the first site dating back to the Coptic civilization was discovered, which is located 15 kilometers north of the city of Gafsa, and since then until today, the Gafsa region has witnessed a multiplicity of research and discoveries, resulting in the collection of a huge amount of information, especially those related to the names of locations and places. However, we face many challenges, especially in dealing with name-by-name similarities and overlaps in geographical indications, which requires intervention and careful handling. In addition to errors resulting from the initial data, there is also a lack of important elements, such as the identification of archaeological sites that have not yet been discovered, or to which sufficient attention has not been given attention. In this article, we will seek to address these issues using a variety of tools and techniques, including geographic and archaeological data, field visits, and applications of modern technology. By utilizing these methods in an integrated manner, we aspire to improve the accuracy of site and place recognition, and to provide more complete and accurate data, which enhances our understanding and documentation of prehistoric history in a better and more comprehensive way.